A review on aluminium matrix composite with various reinforcement particles and their behaviour. (2020) - Arunkumar, S.; Subramani Sundaram, M.; Suketh kanna, K.M.; Vigneshwara, S.
Abstract: Aluminium metal matrix composites have the potential to satisfy the recently developed demands of advanced engineering applications. The improved mechanical property reduced weight, increased strength, compliance to conventional processing technique and potentially reduces the production cost of aluminum composites helps to meet industrial and engineering demands. The behavior of these materials is heavily influenced by the composition of particulate-reinforcements in the metal matrix since some of the processing parameters are associated with the reinforcing particles. Many combinations of reinforcement particles have been experimented and conceptualized on the design of aluminum hybrid composites. This paper is an attempt to review the different particulate-reinforcement used and their combinations in the processing of aluminum matrix composites and how it affects the mechanical and wear behaviors of these materials. The methodology of various papers has been studied and their corresponding conclusions were included. The major reinforcement particles used in Synthesizing these materials are briefly discussed and scope for new research areas for the purpose of further improvement on aluminum composites are identified.